1987
DOI: 10.1182/blood.v69.1.338.338
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody to the membrane glycoprotein complex CD18 inhibits polymorphonuclear leukocyte accumulation and plasma leakage in vivo

Abstract: Previous in vitro findings suggest a critical role for the polymorphonuclear leukocyte (PMN) membrane glycoprotein complex CD18 in PMN adherence and chemotaxis. We examined the effect of the murine monoclonal antibody (MoAb) 60.3, recognizing CD18, on induced PMN accumulation in vivo. Rabbits were pretreated with MoAb 60.3, and the chemotactic factors fMLP, leukotriene (LT)B4, and C5a, as well as histamine, were injected intradermally; 4 hours later, plasma leakage (125I-albumin) and the PMN accumulation (myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 478 publications
(78 citation statements)
references
References 10 publications
6
72
0
Order By: Relevance
“…In contrast, we found that inhibition of Mac-1 and LFA-1 had no effect on NET-evoked neutrophil rolling. Our findings are also supported by numerous studies showing that targeting Mac-1 and LFA-1 reduces leukocyte adhesion while having no effect on leukocyte rolling (Arfors et al, 1987;Becker, Garman, Whitcup, Planck, & Rosenbaum, 2001 et al, 2007;Nolte et al, 1994;Riaz et al, 2002;von Andrian et al, 1991). In addition, considering the dominating role of P-selectin and PSGL-1, it is perhaps not surprising that β 2 -integrins appear to play no role in NET-induced-provoked neutrophil rolling.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, we found that inhibition of Mac-1 and LFA-1 had no effect on NET-evoked neutrophil rolling. Our findings are also supported by numerous studies showing that targeting Mac-1 and LFA-1 reduces leukocyte adhesion while having no effect on leukocyte rolling (Arfors et al, 1987;Becker, Garman, Whitcup, Planck, & Rosenbaum, 2001 et al, 2007;Nolte et al, 1994;Riaz et al, 2002;von Andrian et al, 1991). In addition, considering the dominating role of P-selectin and PSGL-1, it is perhaps not surprising that β 2 -integrins appear to play no role in NET-induced-provoked neutrophil rolling.…”
Section: Discussionsupporting
confidence: 85%
“…Vascular injury is, in part, the consequence of CDll/CD18-mediated adherence of leukocytes to vascular endothelium. This is evidenced by the observation that mAb 60.3 prevented both accumulation of PMNL in lung vasculature and the subsequent lung injury in an experimental model of ARDS [49]. Because theta toxin promoted vascular leukostasis in vivo, and because toxin-induced enhancement of PMNL adherence to gelatin matrices was inhibited by anti-CD18 antibodies, this mechanism may contribute to vascular injury in C. perfringens infection.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, rat MNLs appear to be less responsive than rabbit MNLs, because in rabbits the increase in venular MNL concentration 5 and 30 min after preparation was approximately 50% of the PMNL value, while we observed no increase in MNL concentration at 15 min and only a minor rise at 30 min after exteriorization of the rat mesentery. Thirdly, Fiebig and co-workers found that systemic treatment with an anti-CD18 mAb, which blocks ®rm leukocyte adhesion but not rolling in rabbit tissues (Arfors et al, 1987;von Andrian et al, 1991), reduced the preparation-induced total venular leukocyte concentration by 60%. This suggests that mesenteric exteriorization in the rabbit results in a relatively large number of ®rmly adherent leukocytes, as compared to only &10% ®rmly adherent cells in the rat mesentery, where the fraction of these non-rolling leukocytes was directly documented by intravital microscopy immediately before ®xation for histology.…”
Section: Discussionmentioning
confidence: 99%